STUDY OF MAGNETISM IN OSMIUM CLUSTER COMPOUNDS AS MOLECULAR-MODELS FOR SMALL METALLIC PARTICLES - Johnson, D; Benfield, R; Edwards, P; Nelson, W; Vargas, M (1985)
The magnetic susceptibilities of a series of cluster carbonyl compounds of osmium have been measured by a high-sensitivity Faraday method and the evolution of certain aspects of 'metallic' behaviour in the high-nuclearity clusters is revealed by a steady increase in the excess molecular susceptibility as the cluster size increases. We also consider here 'metallic' status in the cluster compounds of other transition elements. © 1985 Nature Publishing Group.